Study on a Few Traditional Fermented Food Practices of Mising Community of Dhemaji District, Upper Assam, India - Pegu, Bhaba Kumar; Sarmah, Puja; Yein, Jelshing; Sanong, James (Asian Journal of Biological and Life Sciences)
Among different ethnic tribes in the Himalayan region of India indigenous fermented foods is a significant part of the diet. For the development of various flavours, aromas and textures fermentation is considered one of the oldest and most economical methods. Through this method, different microbial populations are manipulated to produce biologically enriched food.[1] One of the oldest methods for processing and preserving food is fermentation has been known worldwide from ancient civilizations. Fermentation of food materials is used as a way for enhancement of flavour, and preservation of food by the ethnic and indigenous people of this region from time immemorial.[2] Microbes are the major ingredient in the production of different fermented food and beverages. By using different substrates and non-pathogenic micro-organisms as starters fermented foods are prepared, and these are then sold in the local market for consumption.[3] All non-Aryan ethnic tribes of Northeast India had a tradition of having their brand of homemade traditional fermented food. Indigenous fermented food of this region is closely connected to practically all aspects of their socio-cultural, and religious ceremonies and ritual events.[4] The different ethnic tribe from various region of India especially people from North-East India has very distinct and region-specific procedure for fermenting food and utilizing various specific substrate.[5–7] The Mising tribes belong to the Indo-Mongoloid group of the Indian population. Read more . . .